Comprehensive Normative Analysis Concerning Indonesia Domain Name Legal Policy - Musyarri, Fazal Akmal (Universitas Airlangga, 2025)
The world is moving toward the digitalization period in the frame of the Industrial Revolution 4.0. Prof. Klaus Schwab stated that the Website was included in matters affecting the current direction of civilization in society. In the Website, the Domain Name is an important component that serves as an easy-to-remember referral address. Indonesia has its own Domain Name with the .id extension or often referred to as the Indonesia Domain Name. The regulation is scattered in several laws. By using Normative Juridical research methods and statutory and conceptual approaches, the author intends to map the Indonesia Domain Names laws. The results have not only mapped the concept map of the Indonesia Domain Name regulations, but also analyzed the legal issues surrounding it. This study is expected to be a representation for the government to create a more comprehensive Indonesia Domain Name law so that it can lead to legal certainty conditions for Indonesia Domain Name Registrants in the future as ius constituendum of Information and Communication Technology Law.